Mogamulizumab efficacy is underscored by its associated rash that mimics cutaneous T‐cell lymphoma: a retrospective single‐centre case series. (20th October 2021) - Trum, N.A.; Zain, J.; Martinez, X.U.; Parekh, V.; Afkhami, M.; Abdulla, F.; Carson, K.R.; Rosen, S.T.; Bennett, C.L.; Querfeld, C.
Summary: Background: Mogamulizumab is a humanized antibody against chemokine receptor type 4. It was recently approved by the US Food and Drug Administration for relapsed or refractory mycosis fungoides (MF) and Sézary syndrome (SS). The most commonly reported adverse event in the phase III licensing trial was drug eruption (28%), now termed mogamulizumab‐associated rash (MAR). Clinical recommendations about MAR and its treatment differ between the current package insert and postapproval insights reported from two single‐centre studies that focused on its characterization, but less so on outcomes and clinicopathological differentiation from cutaneous T‐cell lymphoma (CTCL). Objectives: To describe our experience in the diagnosis of MAR and treatment of patients with CTCL with mogamulizumab. Methods: This is a single‐centre retrospective case series study. Results: We found a higher incidence of MAR in patients with CTCL (17 of 24, 68%) than previously reported. MAR development is associated with complete (11 of 17) or partial (four of 17) responses, with an overall response rate of 88%, compared with 29% (two of seven) in patients without MAR. Diagnosis of MAR may be obscured by its ability to mimic key CTCL features both clinically and histologically, but an absence of T‐cell‐receptor clonality and relatively decreased CD4 : CD8 ratio compared with baseline lesions strongly favour MAR over recurrent disease. Conclusions: MAR has the potential to create a significant management problem for patients on mogamulizumab. Misidentification of MAR as recurrent CTCL may detrimentally result in the premature discontinuation of mogamulizumab in patients whose disease is historically hard to treat. Thorough clinicopathological investigation of new lesions during treatment with mogamulizumab is required to inform ideal treatment decisions and achieve better outcomes. Abstract : What is already known about this topic? Previous descriptions of mogamulizumab‐associated rash (MAR) include case reports or series and two subgroup analyses of the mogamulizumab‐approving MAVORIC clinical trial. Previous reports lacked clinical outcome data or robust clinicopathological differentiation from recurrent cutaneous T‐cell lymphoma (CTCL). Patients with Sézary syndrome develop MAR more often than those with mycosis fungoides. What does this study add? Outside of clinical trial constraints, we describe a Sézary syndrome‐predominant cohort of patients with CTCL who developed both a higher incidence of MAR and a higher overall response rate to mogamulizumab than previously reported. We describe the diverse manifestations of MAR, including four histopathological and five clinical patterns, in relation to other reports. We confidently differentiate between MAR and recurrent CTCL through molecular testing and provide our diagnostic methodology. Linked Comment:  G. Blanchard and E. Guenova. Br J Dermatol 2022; 186:15–16 . Plain language summary available online